2009
DOI: 10.1021/es9014234
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Site Surface Complexation Constants for Lanthanide Adsorption to Bacteria As Determined by Experiments and Linear Free Energy Relationships

Abstract: Bacteria are abundant in many natural and engineered environments where they are thought to exert important controls on the cycling, mobility, bioavailability, and toxicity of metal contaminants. In order to probe their role in moderating the behavior of lanthanides, pH-dependent adsorption edges of 13 individual lanthanides and yttrium to the Gram-negative bacterium Pantoea agglomerans were used to generate discrete site surface complexation constants. The calculated surface complexation constants were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…The resulting REE pattern exhibits a tetrad effect and a prominent enrichment in HREE (from Er to Lu). Based on EXAFS evidence and modeling calculations, this shape was further attributed to the binding of REE as inner sphere complexes with carboxylic and multiple phosphate sites occurring on the surface cells (Takahashi et al 2010;Ngwenya et al 2010;Martinez et al 2014). Simpson et al (2007) suggested that bacterially derived biomass could constitute more than 50 % of the total soil organic carbon in aerobic soils.…”
Section: Impact Of Biological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting REE pattern exhibits a tetrad effect and a prominent enrichment in HREE (from Er to Lu). Based on EXAFS evidence and modeling calculations, this shape was further attributed to the binding of REE as inner sphere complexes with carboxylic and multiple phosphate sites occurring on the surface cells (Takahashi et al 2010;Ngwenya et al 2010;Martinez et al 2014). Simpson et al (2007) suggested that bacterially derived biomass could constitute more than 50 % of the total soil organic carbon in aerobic soils.…”
Section: Impact Of Biological Parametersmentioning
confidence: 99%
“…Several authors have demonstrated the ability of the bacterial cell surface to bind REE (Takahashi et al 2005(Takahashi et al , 2010Ngwenya et al 2009Ngwenya et al , 2010. The resulting REE pattern exhibits a tetrad effect and a prominent enrichment in HREE (from Er to Lu).…”
Section: Impact Of Biological Parametersmentioning
confidence: 99%
“…In his deeply insightful paper, Elderfield (1988) suggested cause for concern over this conjecture: not for shallow REE adsorption, but in light of a mechanism for desoprtion at depth. For many trivalent cations the pH-edge/Langmuir-front for adsorption onto particle surfaces lies well under a pH of 7 (Morel and Hering, 1993;Ngwenya et al, 2010); thus, over a typical oceanic pH range of 7.6 and 8.2 desorption is unlikely. The thermodynamics of desorption become even less favorable as the increasing dissolved concentration at depth would tend to push the equilibrium toward further adsorption (reiterating arguments posed by Elderfield, 1988).…”
Section: Modern Ocean Rees and Nd Isotopesmentioning
confidence: 99%
“…The thermodynamics of desorption become even less favorable as the increasing dissolved concentration at depth would tend to push the equilibrium toward further adsorption (reiterating arguments posed by Elderfield, 1988). Moreover, given free Nd is <16% of the total dissolved Nd (Millero, 1992;Schijf et al, 2015), and surface adsorption coefficients are typically not exceptionally high (in the range of 3 to 5 onto carboxyl and moncarboxylic groups; Smith and Martell, 1989;Byrne and Kim, 1990;Ngwenya et al, 2010), the potential for REE transfer from the shallow to deep ocean via particle surface scavenging should be limited (Elderfield and Greaves, 1982;Stichel et al, 2015).…”
Section: Modern Ocean Rees and Nd Isotopesmentioning
confidence: 99%
“…Lanthanum ions show better performance as they prefer to bind through phosphate sites compared with carboxyl complexation at low pH (Ngwenya et al, 2010), which is provided during sample loading and washing. Thus they reduce the binding of acidic residues through carboxylic sites.…”
Section: Phosphopeptide Enrichment By Terpolymer-imacmentioning
confidence: 99%